High-strength anti-aging wood electric heating composite material and preparation method thereof
By using silanized modified delignification wood fibers, multi-wall carbon nanotubes and nanosilver wires, low-melting point alloys and high-density polyethylene in wood electrothermal composites, the insufficient conductivity and thermal conductivity of existing materials are solved. The problem of this is that wood electric heating composite materials with high strength, high aging resistance and high efficiency electric heating conversion are achieved.
Patent Information
- Application Number
- CN202411667149.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing wood electric thermal composite materials have problems such as insufficient conductivity and thermal conductivity, poor glue strength, low mechanical strength, poor moisture resistance, and easy aging, resulting in limited application.
The silanized modified delignant wood fiber is used as the matrix, multi-walled carbon nanotubes and nanosilver wires are used as the conductive heating units, low-melting point alloys are used as the thermally conductive reinforced phase, and high-density polyethylene is used as the binder, through mixing and heating Pressure process to prepare high-strength, aging-resistant wood electric heating composite materials.
Achieved efficient electric heat conversion efficiency, with a thermal conductivity between 0.65 and 1.2W/(m.K), a bending strength of 85 to 96MPa, an internal bonding strength of 5.6 to 8.5MPa, which has fast thermal conductivity, moldability, excellent stability and Aging resistance, suitable for applications in the field of wood electric heating.
Smart Images

Figure CN119458548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wood electrothermal composite material technology, and in particular to a high-strength aging-resistant wood electrothermal composite material and a preparation method thereof. Background Art
[0002] Wood electric heating composite materials use conductive materials as heating units. After being compounded with wood materials, they generate Joule heat under load voltage, giving wood materials electric heating functions. They can be applied to electric heating wood floors, electric heating wood wall panels, electric heating furniture and other products. At present, electric heating elements are mostly directly compounded with wood using heating elements such as low-temperature cables, carbon fiber paper, carbon crystal heating sheets, and resin electric heating films. However, these heating materials have problems such as poor bonding strength with wood substrates, low mechanical strength, low thermal conductivity, poor moisture resistance, and easy aging. In order to improve the rapid response of electric heating, conductive units of different forms and properties are mainly blended. Through filling, stacking and contact between conductive units, a more continuous and compact conductive channel is formed, thereby achieving a higher stable temperature with a lower voltage. However, the electrical and thermal conductivity of wood materials is poor. To obtain efficient wood electric heating composite materials, it is necessary to have high electrical conductivity and thermal conductivity at the same time to effectively generate and dissipate Joule heat. In addition, inputting low voltage is crucial to ensure the safety of electric heating composite materials. Using too high voltage poses potential safety hazards. At the same time, too low heating efficiency usually leads to lower heating temperature and heating rate, which makes the prepared composite material lack excellent electrothermal response characteristics, which will limit the application of wood electrothermal composite materials. Therefore, how to reduce the input voltage to obtain efficient electrothermal conversion efficiency, and have reliable stability and mechanical strength and large-scale production is still a technical problem faced by wood electrothermal composite materials. Therefore, it is necessary to develop a high-strength, high-aging-resistant wood electrothermal composite material. Summary of the invention
[0003] The present invention is developed in view of the above problems, and aims to provide a high-strength and high-aging-resistant wood electrothermal composite material and a preparation method thereof.
[0004] The first aspect of the present invention relates to a method for preparing a high-strength, aging-resistant wood-based electrothermal composite material, which comprises:
[0005] (1) adjusting the pH value of a 2-5 wt% sodium chlorite aqueous solution to 4.6-5.0 by using 10-12 mol / L glacial acetic acid, immersing washed and dried wood fibers in the acid-adjusted sodium chlorite aqueous solution, wherein the material-liquid mass ratio is 1:(50-60), and then treating the fibers in a water bath at 40-45° C. for 2-3 h, taking the fibers out, washing, and drying the fibers to obtain delignified wood fibers;
[0006] (2) Mixing delignified wood fiber and KH590 silane / acetone solution in a mass ratio of 1:(9-10) at 45-55°C for activation treatment for 4-6 hours, wherein the mass ratio of KH590 silane / acetone is (5-8):(25-40), so that the surface of the delignified wood fiber is silanized, taking it out and leaving it for more than 1 hour to allow all the acetone to volatilize, and then drying it at 60-65°C for 6-8 hours;
[0007] (3) slowly adding multi-walled carbon nanotubes and nanosilver wires in a mass ratio of 5:(2-5) into N,N-dimethylformamide, wherein the material-liquid mass ratio is (5-20):(80-95), magnetically stirring for 4-5 hours, and then performing water-soluble ultrasonic dispersion for 30-50 minutes, and then continuing magnetic stirring for 4-5 hours to obtain a multi-walled carbon nanotube / nanosilver wire mixed solution;
[0008] (4) applying a multi-walled carbon nanotube / nanosilver wire mixed solution with a mass ratio of (10-30):(5-10) to the delignified wood fiber modified by silane by high-pressure atomization, mixing and dispersing for 30-50 minutes by a nano-disperser during the high-pressure atomization process to obtain a wood fiber loaded with multi-walled carbon nanotube / nanosilver wire, and drying the wood fiber at a temperature of 60-65° C. for 6-10 hours after taking it out;
[0009] (5) The KH590 coupling agent and an ethanol aqueous solution with a concentration of 92-95 wt% are magnetically stirred at room temperature for 1-2 h to prepare a silane coupling agent / ethanol / water solution with a coupling agent mass fraction of 5-7%, and a powdered multi-component low melting point alloy Sn is added. 16 Bi 52 Pb 32 Add to silane coupling agent / ethanol / water solution and stir and blend for 15-40 minutes. The material-liquid mass ratio is 1:(100-120). The melting point of the alloy is 95-97°C and the density is 9.56-9.59 g / cm 3 , the mass ratio of Sn / Bi / Pb is (43-50):(6-9):(42-51), so as to modify the surface of the multi-element low melting point alloy, form a Si monolayer on the alloy surface, and then dry it after taking it out;
[0010] (6) blending and grinding the surface-modified multi-element low-melting-point alloy and high-density polyethylene powder in a mass ratio of 1:(5-6) in a mortar to obtain a low-melting-point alloy / polyethylene mixture;
[0011] (7) mixing a low melting point alloy / polyethylene mixture with a mass ratio of (5-20):(80-100) and wood fibers loaded with carbon nanotubes / nanosilver wires, and kneading the mixture at 150-160° C. for 30-40 min. After kneading, the mixture is taken out and crushed into a particle size of 100-300 meshes;
[0012] (8) After the crushed mixture is paved, it is hot-pressed at a temperature of 180 to 190° C., a pressure of 5 to 10 MPa, and a time of 10 to 12 min, so that the low-melting-point alloy and the high-density polyethylene melt during the hot-pressing process, and the nano-conductive material and the wood fiber are bonded. After the mixture is completely cooled and solidified, the composite material is taken out to obtain the wood electrothermal composite material.
[0013] Furthermore, in (1), the wood fiber is eucalyptus or poplar fiber, with a length distribution of 0.5-2.5 mm, a diameter distribution of 0.05-0.25 μm, an aspect ratio of 8-16, and is washed with deionized water and then dried at 103-105° C. for 8-10 hours.
[0014] Furthermore, in (3), the multi-walled carbon nanotubes have a length of 1 to 10 μm, a diameter of 8 to 50 nm, an inner diameter of 3 to 12 nm, and the nanosilver wires have a length of 20 to 100 μm, a diameter of 20 to 90 nm, and a purity of 98%.
[0015] Furthermore, in (3), multi-walled carbon nanotubes and nanosilver wires are added into N,N-dimethylformamide at a rate of 0.2 g / 10 s.
[0016] Furthermore, in (3), the magnetic stirring speed is 800 to 1500 rpm / min, and the ultrasonic frequency is 120 to 130 KHz.
[0017] Furthermore, in (4), the high-pressure atomization pressure is 0.2 to 0.7 MPa.
[0018] Furthermore, in (4), the nano-disperser adopts ultrasonic high-frequency vibration mode, with a power of 600-800 W, an ultrasonic frequency of 150-180 KHz, a vibration frequency of 0.05-0.08 Hz, and an amplitude of 100-150 μm.
[0019] Furthermore, in (5), the magnetic stirring speed is 800 to 1500 rpm / min, and the stirring and blending speed is 800 to 1500 rpm / min.
[0020] Furthermore, in (5), the alloy has a melting point of 96°C and a density of 9.562 g / cm 3 .
[0021] Furthermore, the mass ratio of Sn / Bi / Pb is (43.6-49.6):(6-9):(42.4-50.4), and further, the mass ratio is 48.6:6:45.4.
[0022] Furthermore, in said (6), the powder is ground to a particle size of 100 to 300 meshes.
[0023] Furthermore, in (6), the density of the high-density polyethylene powder is 1.91 to 1.96 g / cm 3 .
[0024] Furthermore, in the step (7), the uniform mixing is carried out at a rotation speed of 800 to 1500 rpm / min.
[0025] Furthermore, in the above (7), kneading is performed in a torque rheometer at a rotation speed of 250 to 300 rpm / min.
[0026] Furthermore, in (8), the paving density is 1.5 to 2.0 g / cm 3 .
[0027] Furthermore, in (8), the paving thickness is 0.8 to 1.5 mm.
[0028] The present invention also provides a high-strength, ageing-resistant wood electrothermal composite material prepared by any of the above preparation methods.
[0029] The present invention uses silanized delignified wood fiber as a matrix, multi-walled carbon nanotubes and nano silver wires as synergistic conductive heating units, a low melting point alloy as a thermal conductivity enhancement phase, and high-density polyethylene as an adhesive to prepare a high-strength, aging-resistant wood electrothermal composite material through mixing and hot pressing processes.
[0030] The present invention uses delignified wood fiber as the main matrix, multi-walled carbon nanotubes and nano silver wires as the conductive heating unit, low melting point alloy as the thermal conductivity enhancement phase, and high-density polyethylene as the adhesive. The low melting point alloy, multi-walled carbon nanotubes and nano silver wires synergistically enhance the electrothermal effect and mechanical strength of the composite material. The prepared wood fiber-based electrothermal composite material has an applied voltage of 8 to 24V, a heating temperature of 45 to 144°C, an electrothermal radiation conversion efficiency of more than 97%, a temperature non-uniformity of less than 5°C, a bending strength of 85 to 96MPa, an internal bonding strength of 5.6 to 8.5Mpa, and a thermal conductivity of 0.65 to 1.2W / (mK). It has the advantages of rapid thermal conductivity, formability, excellent stability and aging resistance, and easy industrial production, and is conducive to application in the field of wood electric heating.
[0031] Multicomponent low melting point alloy Sn 16 Bi 52 Pb 32When mixed into high-density polyethylene, the temperature of each part tends to be consistent, which is more conducive to improving thermal conductivity. However, the complex lattice of the multi-element alloy sacrifices the conductivity. By modifying the KH590 coupling agent to form a semiconductor monolayer on the periphery of the alloy, it is beneficial to induce additional electrons / holes and increase the carrier concentration, thereby improving the conductivity. In addition, the KH590 coupling agent provides the dispersibility of the alloy and shows better mechanical properties. Therefore, the addition of the KH590 coupling agent brings about a synergistic technical effect.
[0032] Nano silver wires and wood fibers are combined to prepare electric heating composite materials. Since wood fibers are highly hygroscopic as a matrix, they are used in a hot and humid environment, causing rapid oxidation of the nano silver wires, resulting in damage to the conductive properties, decreased electrothermal effect, and serious conductive short circuits, causing local high-temperature carbonization of the wood electrothermal composite materials. Adding low-melting-point alloys to wrap the nano silver wires and wood fibers isolates the wood fibers and nano silver wires from moisture absorption and oxidation during the hot and cold cycle process, significantly improving the stability of the electric heating performance and aging resistance of the wood electrothermal composite materials. After 720 hours of accelerated aging at 65-70°C and 80-90% humidity, the electrothermal and mechanical properties are stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a physical picture of the wood-based electrothermal composite material of Preparation Example 1 according to an embodiment of the present invention.
[0034] Figure 2 This is a color temperature diagram of the wood-based electrothermal composite material prepared in Example 1 according to an embodiment of the present invention after being tested at different voltages. DETAILED DESCRIPTION
[0035] In the process description of the present invention, there will be some numerical values related to temperature or pressure, process change rate, etc. For example, taking temperature as an example, those skilled in the art should know that when it is mentioned that the actual meaning of carrying out a reaction at a certain temperature is that the control of temperature is not an absolute constant temperature, but may or even often will have a certain fluctuation, which may exceed one degree or even more in some cases, as long as the implementation purpose can be achieved. The amplitude of temperature change and the accuracy of temperature control are based on the scope that can be understood by those skilled in the art.
[0036] In addition, the temperature defined herein may be the input for temperature control on the equipment used, and the temperature at a certain point in the actual process depends on the particularity of the equipment and the reaction conditions at the time. The defined temperature may also be the target of the operator's instruction, which may involve a temperature change time in actual control, or even a process of repeated ups and downs. For example, when the temperature is detected to be lower than the defined temperature, the reactor is heated, and when it is higher than the defined temperature, the reactor is cooled, so as to maintain the command temperature as a whole.
[0037] When the concept of normal temperature or room temperature is mentioned, it usually refers to 22-25°C, and sometimes it may be between 20-28°C depending on the process. 25°C is used in the implementation of the present invention, but it should be considered that the above temperature range can achieve the corresponding effect. In actual industry, different fields have different understandings of normal temperature or room temperature, but from the perspective of the implementation and application of patent law, it should be viewed as limited to achieving the purpose of the invention, and should not be limited to the narrow experience range of a certain field.
[0038] In the present invention, if there is no temperature or room temperature limit mentioned for some processes, it should generally be considered that they are carried out at normal temperature or room temperature. Those skilled in the art can control the process conditions without special understanding, unless otherwise specified or those skilled in the art should understand the special details.
[0039] In the present invention, unless otherwise stated, the numerical range "A to B" means greater than A (greater than or equal to A) and less than B (less than or equal to B).
[0040] Preparation Example 1:
[0041] 1. The eucalyptus fibers were screened, with a length distribution of 0.5-2.5 mm, a diameter distribution of 0.05-0.25 μm, and an aspect ratio of 8-16. After being washed with deionized water, they were dried in an oven at 103°C for 8 hours.
[0042] 2. A 2wt% sodium chlorite aqueous solution was prepared with deionized water and sodium chlorite in a mass ratio of 98:2, and the pH value of the sodium chlorite aqueous solution was adjusted to 5.0 by 10 mol / L glacial acetic acid. Eucalyptus fiber was immersed in the sodium chlorite aqueous solution with a solid-liquid bath ratio of 1:50, and then taken out after heating at 40°C for 2 hours, washed with deionized water, and dried to obtain delignified eucalyptus fiber.
[0043] 3. Put KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane) into acetone to prepare a KH590 silane / acetone solution with a mass ratio of 7:30. Place the delignified eucalyptus fiber and KH590 silane / acetone solution in a mass ratio of 1:9 in a water bath at 50°C for activation for 4 hours. After the surface of the eucalyptus fiber is silanized and modified, take it out, leave it for 1 hour to allow all the acetone to evaporate, and dry it in a 60°C oven for 6 hours.
[0044] 4. Add multi-walled carbon nanotubes and nanosilver wires in a mass ratio of 5:2 at a mass concentration of 5wt% at a rate of 0.2g / 10s, wherein the multi-walled carbon nanotubes have a length of 5μm, a diameter of 30nm, an inner diameter of 6nm, the nanosilver wires have a length of 50μm, a diameter of 50nm, and a purity of 98%, and then carry out magnetic stirring at a speed of 1000rpm / min for 4h, ultrasonic dispersion at a frequency of 120KHz in water for 30min, and then continue to carry out magnetic stirring at a speed of 1000rpm / min for 4h to obtain a mixed solution of multi-walled carbon nanotubes and nanosilver wires.
[0045] 5. The mixed liquid of multi-walled carbon nanotubes and nano-silver wires was applied to the silane-modified eucalyptus fibers by high-pressure atomization, with a mass ratio of 20:7. The high-pressure atomization process was mixed and dispersed by a nano-disperser for 30 minutes, wherein the high-pressure atomization pressure was 0.5 MPa. The nano-disperser adopted ultrasonic high-frequency vibration mode with a power of 700 W, an ultrasonic frequency of 160 KHz, a vibration frequency of 0.07 Hz, and an amplitude of 120 μm, thereby obtaining eucalyptus fibers loaded with multi-walled carbon nanotubes / nano-silver wires, which were taken out and dried at 60°C for 6 hours.
[0046] 6. KH590 coupling agent (γ-mercaptopropyltrimethoxysilane) and 95% ethanol aqueous solution were magnetically stirred at room temperature at a speed of 1000 rpm / min for 1 hour to prepare a silane coupling agent solution with a mass fraction of 5%. 16 Bi 52 Pb 32 Alloy, melting point 96°C, density 9.562g / cm 3 , Sn / Bi / Pb mass ratio of 48.6:6:45.4) was added to the silane coupling agent solution and stirred at a speed of 1000 rpm / min for 20 minutes, and the material-liquid mass ratio was 1:100, so as to modify the surface of the multi-element low-melting-point alloy, form a Si monolayer on the alloy surface, and then take it out and dry it.
[0047] 7. The surface-modified low-melting-point alloy powder and high-density polyethylene powder were blended and ground in a mortar at a mass ratio of 1:5 to obtain a low-melting-point alloy / high-density polyethylene powder mixture, wherein the high-density polyethylene powder had a density of 1.91 g / cm 3 .
[0048] 8. A low melting point alloy / polyethylene mixture with a mass ratio of 5:95 was mixed with eucalyptus fibers loaded with carbon nanotubes and nanosilver wires, and the mixture was fully mixed at a speed of 1000 rpm / min in a high-speed mixer and then placed in a torque rheometer at a temperature of 150°C and a speed of 250 rpm / min for mixing for 30 minutes. After mixing, the mixture was taken out and crushed into a particle size of 200 mesh using a small pulverizer.
[0049] 9. Put the multi-component crushed mixed material into the mold, with a design format of 200×200mm, a paving thickness of 0.8mm, and a density of 1.8g / cm 3 , formed by hot pressing of a flat vulcanizer, the hot pressing temperature is 180℃, the pressure is 8MPa, and the time is 10min. During the hot pressing process, the low melting point alloy and high density polyethylene melt, so that the nano conductive material and wood fiber are bonded. After complete cooling and solidification, the composite material is taken out. Figure 1 Shown is a physical picture of the electrothermal composite material prepared in this example.
[0050] 10. The prepared wood electrothermal composite material is subjected to a low voltage of 8 to 24 V, and the heating time is 10 to 12 minutes. The stable temperature can reach 45 to 144°C, the electrothermal radiation conversion efficiency is more than 97%, the temperature unevenness is less than 5°C, and it has fast heat transfer performance, and the thermal conductivity is 0.65 to 1.2 W / (mK). Figure 2 The example cites the color temperature diagram of the electrothermal composite material prepared in this example when tested at 8V and 12V voltages, and has good flexural strength and water and weather resistance, with a flexural strength of 85-96MPa and an internal bonding strength of 5.6-8.5MPa. After accelerated aging with wet heat for 720h, a temperature of 65°C, and a humidity of 80%, the electrothermal and mechanical properties are stable.
[0051] Preparation Example 2:
[0052] 1. The poplar wood fibers were sieved, with a length distribution of 0.5-2.5 mm, a diameter distribution of 0.05-0.25 μm, and an aspect ratio of 8-16. After washing with deionized water, they were dried in an oven at 105°C for 10 hours.
[0053] 2. Prepare a 5wt% sodium chlorite aqueous solution with deionized water and sodium chlorite in a mass ratio of 95:5, and adjust the pH value of the sodium chlorite aqueous solution to 4.8 with 12mol / L glacial acetic acid. Soak the poplar fiber in the sodium chlorite aqueous solution with a solid-liquid bath ratio of 1:60, heat it in a water bath at 45°C for 3h, take it out, wash it with deionized water, and dry it to obtain delignified poplar fiber.
[0054] 3. Put KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane) into acetone to prepare a KH590 silane / acetone solution with a mass ratio of 5:25, place the delignified poplar fiber and KH590 silane / acetone solution in a mass ratio of 1:10 in a water bath at 45°C for activation for 5 hours, and remove the poplar fiber after silanization modification of the surface. Place the fiber for 2 hours to allow the acetone to evaporate completely, and then place it in a 65°C oven to dry for 8 hours.
[0055] 4. Multi-walled carbon nanotubes and nanosilver wires in a mass ratio of 5:3 were added to N,N-dimethylformamide at a mass concentration of 10wt% at a rate of 0.2g / 10s, wherein the multi-walled carbon nanotubes had a length of 1μm, a diameter of 8nm, an inner diameter of 3nm, the nanosilver wires had a length of 20μm, a diameter of 20nm, and a purity of 98%, and then magnetically stirred at a speed of 800rpm / min for 4h, ultrasonically dispersed in water at a frequency of 120KHz for 40min, and then magnetically stirred at a speed of 800rpm / min for 5h to obtain a mixed solution of multi-walled carbon nanotubes and nanosilver wires.
[0056] 5. The mixed liquid of multi-walled carbon nanotubes and nano-silver wires was applied to the silane-modified poplar fibers by high-pressure atomization, with a mass ratio of 10:5. The high-pressure atomization process was mixed and dispersed by a nano-disperser for 40 minutes, wherein the high-pressure atomization pressure was 0.2 MPa. The nano-disperser adopted ultrasonic high-frequency vibration mode with a power of 600 W, an ultrasonic frequency of 150 KHz, a vibration frequency of 0.05 Hz, and an amplitude of 100 μm, thereby obtaining poplar fibers loaded with multi-walled carbon nanotubes / nano-silver wires, which were taken out and dried at 65°C for 8 hours.
[0057] 6. KH590 coupling agent (γ-mercaptopropyltrimethoxysilane) and 92% ethanol aqueous solution were magnetically stirred at 800 rpm / min at room temperature for 2 h to prepare a silane coupling agent solution with a mass fraction of 5%. 16 Bi 52 Pb 32 Alloy, melting point 95°C, density 9.560g / cm 3 , Sn / Bi / Pb mass ratio of 49.6:7:43.4) was added to the silane coupling agent solution and stirred at a speed of 800 rpm / min for 15 minutes, and the material-liquid mass ratio was 1:110, so as to modify the surface of the multi-element low-melting-point alloy, form a Si monolayer on the alloy surface, and then take it out and dry it.
[0058] 7. The surface-modified low-melting-point alloy powder and high-density polyethylene powder were blended and ground in a mortar at a mass ratio of 1:6 to obtain a low-melting-point alloy / high-density polyethylene powder mixture, wherein the high-density polyethylene powder had a density of 1.96 g / cm 3 .
[0059] 8. A low melting point alloy / polyethylene mixture with a mass ratio of 10:90 was mixed with poplar fibers loaded with carbon nanotubes and nanosilver wires, and the mixture was fully mixed at a speed of 800 rpm / min in a high-speed mixer, and then placed in a torque rheometer and mixed at a temperature of 160°C and a speed of 280 rpm / min for 40 minutes. After mixing, the mixture was taken out and crushed into a particle size of 300 mesh using a small pulverizer.
[0060] 9. Put the multi-component crushed mixed material into the mold, with a design format of 200×200mm, a paving thickness of 1.0mm, and a density of 1.5g / cm 3 It is formed by hot pressing on a flat vulcanizer at a temperature of 190°C, a pressure of 5 MPa, and a time of 12 minutes. During the hot pressing process, the low-melting-point alloy and high-density polyethylene melt, allowing the nano-conductive material and wood fiber to bond. The composite material is taken out after it is completely cooled and solidified.
[0061] 10. The prepared wood electrothermal composite material is applied with a low voltage of 8 to 24 V, the heating time is 10 to 12 minutes, the stable temperature can reach 56 to 135°C, the electrothermal radiation conversion efficiency is more than 97%, the temperature non-uniformity is less than 3°C, it has rapid heat transfer performance, thermal conductivity coefficient is 0.74 to 1.1 W / (mK), and has good flexural strength and water and weather resistance, flexural strength is 89 to 94 MPa, internal bonding strength is 6.7 to 8.2 MPa, after 720 hours of accelerated aging with wet heat, temperature is 65°C, humidity is 85%, the electrothermal performance and mechanical properties are stable.
[0062] Preparation Example 3:
[0063] 1. The eucalyptus fibers were screened, with a length distribution of 0.5-2.5 mm, a diameter distribution of 0.05-0.25 μm, and an aspect ratio of 8-16. After being washed with deionized water, they were dried in an oven at 103°C for 8 hours.
[0064] 2. A 3 wt% sodium chlorite aqueous solution was prepared with deionized water and sodium chlorite in a mass ratio of 97:3, and the pH value of the sodium chlorite aqueous solution was adjusted to 5.0 by 12 mol / L glacial acetic acid. Eucalyptus fiber was immersed in the sodium chlorite aqueous solution with a solid-liquid bath ratio of 1:55, and then taken out after being heated at 42°C for 2 hours, washed with deionized water, and dried to obtain delignified eucalyptus fiber.
[0065] 3. Put KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane) into acetone to prepare a KH590 silane / acetone solution with a mass ratio of 8:40, place the delignified eucalyptus fiber and KH590 silane / acetone solution in a mass ratio of 1:10 in a water bath at 55°C for activation for 6 hours, and remove the eucalyptus fiber after silanization modification. Place the fiber for 3 hours to allow the acetone to evaporate completely, and then place it in a 63°C oven for drying for 7 hours.
[0066] 4. Multi-walled carbon nanotubes and nanosilver wires in a mass ratio of 5:4 were added to N,N-dimethylformamide at a mass concentration of 15wt% at a rate of 0.2g / 10s, wherein the multi-walled carbon nanotubes had a length of 10μm, a diameter of 50nm, an inner diameter of 12nm, the nanosilver wires had a length of 100μm, a diameter of 90nm, and a purity of 98%, and then magnetically stirred at a speed of 1200rpm / min for 4h, ultrasonically dispersed in water at a frequency of 130KHz for 50min, and then magnetically stirred at a speed of 1200rpm / min for 5h to obtain a mixed solution of multi-walled carbon nanotubes and nanosilver wires.
[0067] 5. The mixed liquid of multi-walled carbon nanotubes and nano-silver wires was applied to the silane-modified eucalyptus fibers by high-pressure atomization, with a mass ratio of 30:10. The high-pressure atomization process was mixed and dispersed by a nano-disperser for 50 minutes, wherein the high-pressure atomization pressure was 0.7 MPa. The nano-disperser adopted ultrasonic high-frequency vibration mode with a power of 800 W, an ultrasonic frequency of 180 KHz, a vibration frequency of 0.08 Hz, and an amplitude of 150 μm, thereby obtaining eucalyptus fibers loaded with multi-walled carbon nanotubes / nano-silver wires, which were taken out and dried at 63°C for 9 hours.
[0068] 6. KH590 coupling agent (γ-mercaptopropyltrimethoxysilane) and 94% ethanol aqueous solution were magnetically stirred at room temperature at a speed of 1200 rpm / min for 2 hours to prepare a silane coupling agent solution with a mass fraction of 7%. 16 Bi 52 Pb 32 Alloy, melting point 97°C, density 9.590g / cm 3 , Sn / Bi / Pb mass ratio 48.6:9:42.4) was added to the silane coupling agent solution and stirred at a speed of 1200 rpm / min for 30 minutes, and the material-liquid mass ratio was 1:120, so as to modify the surface of the multi-element low-melting-point alloy, form a Si monolayer on the alloy surface, and then take it out and dry it.
[0069] 7. The surface-modified low-melting-point alloy powder and high-density polyethylene powder were blended and ground in a mortar at a mass ratio of 1:6 to obtain a low-melting-point alloy / high-density polyethylene powder mixture, wherein the high-density polyethylene powder had a density of 1.95 g / cm 3 .
[0070] 8. A low melting point alloy / polyethylene mixture with a mass ratio of 15:85 was mixed with eucalyptus fibers loaded with carbon nanotubes and nanosilver wires, and the mixture was fully mixed at a speed of 1200 rpm / min in a high-speed mixer and then placed in a torque rheometer at a temperature of 160°C and a speed of 300 rpm / min for mixing for 40 minutes. After mixing, the mixture was taken out and crushed into a particle size of 300 mesh using a small pulverizer.
[0071] 9. Put the multi-component crushed mixed material into the mold, with a design format of 200×200mm, a paving thickness of 1.2mm, and a density of 1.8g / cm 3 It is formed by hot pressing on a flat vulcanizer at a temperature of 190°C, a pressure of 9 MPa, and a time of 12 minutes. During the hot pressing process, the low-melting-point alloy and high-density polyethylene melt, allowing the nano-conductive material and wood fiber to bond. The composite material is taken out after it is completely cooled and solidified.
[0072] 10. The prepared wood electrothermal composite material is applied with a low voltage of 8 to 24 V and a heating time of 10 to 12 minutes. The stable temperature can reach 71 to 139°C, the electrothermal radiation conversion efficiency is more than 97%, the temperature non-uniformity is less than 3°C, it has rapid heat transfer performance, a thermal conductivity of 0.83 to 1.2 W / (mK), and good flexural strength and water and weather resistance, with a flexural strength of 89 to 92 MPa and an internal bonding strength of 6.3 to 7.8 MPa. After accelerated aging with wet heat for 720 hours at a temperature of 70°C and a humidity of 90%, the electrothermal and mechanical properties are stable.
[0073] Preparation Example 4:
[0074] 1. The poplar wood fibers were sieved, with a length distribution of 0.5-2.5 mm, a diameter distribution of 0.05-0.25 μm, and an aspect ratio of 8-16. After being washed with deionized water, they were dried in an oven at 103°C for 8 hours.
[0075] 2. Prepare a 4 wt% sodium chlorite aqueous solution with deionized water and sodium chlorite in a mass ratio of 96:4, and adjust the pH value of the sodium chlorite aqueous solution to 4.6 with 12 mol / L glacial acetic acid. Soak the poplar fiber in the sodium chlorite aqueous solution with a solid-liquid bath ratio of 1:50, heat it in a water bath at 40°C for 2 hours, take it out, wash it with deionized water, and dry it to obtain delignified poplar fiber.
[0076] 3. Put KH590 silane coupling agent (γ-mercaptopropyltrimethoxysilane) into acetone to prepare a KH590 silane / acetone solution with a mass ratio of 6:35. Place the delignified poplar fiber and KH590 silane / acetone solution in a mass ratio of 1:9 in a water bath at 50°C for activation for 5 hours. After the surface of the poplar fiber is silanized and modified, take it out, place the fiber for 4 hours to allow the acetone to evaporate completely, and dry it in a 60°C oven for 8 hours.
[0077] 4. Multi-walled carbon nanotubes and nanosilver wires in a mass ratio of 5:5 were added to N,N-dimethylformamide at a mass concentration of 20wt% at a rate of 0.2g / 10s, wherein the multi-walled carbon nanotubes had a length of 8μm, a diameter of 40nm, an inner diameter of 8nm, the nanosilver wires had a length of 80μm, a diameter of 70nm, and a purity of 98%, and then magnetically stirred at a speed of 1500rpm / min for 5h, ultrasonically dispersed in water at a frequency of 130KHz for 50min, and then magnetically stirred at a speed of 1500rpm / min for 5h to obtain a mixed solution of multi-walled carbon nanotubes and nanosilver wires.
[0078] 5. The multi-walled carbon nanotube and nano-silver wire mixture was applied to the silane-modified poplar fiber by high-pressure atomization, with a mass ratio of 25:8. The high-pressure atomization process was mixed and dispersed by a nano-disperser for 50 minutes, wherein the high-pressure atomization pressure was 0.6 MPa. The nano-disperser adopted ultrasonic high-frequency vibration mode with a power of 700 W, an ultrasonic frequency of 170 KHz, a vibration frequency of 0.07 Hz, and an amplitude of 140 μm, thereby obtaining poplar fiber loaded with multi-walled carbon nanotubes / nano-silver wires, which was taken out and dried at 60°C for 10 hours.
[0079] 6. The KH590 coupling agent (γ-mercaptopropyltrimethoxysilane) and 93% ethanol aqueous solution were magnetically stirred at room temperature at a speed of 1500 rpm / min for 1 hour to prepare a silane coupling agent solution with a mass fraction of 7%. 16 Bi 52 Pb 32 Alloy, melting point 97°C, density 9.562g / cm 3 , Sn / Bi / Pb mass ratio of 43.6:6:50.4) was added to the silane coupling agent solution and stirred at a speed of 1500 rpm / min for 40 minutes, and the material-liquid mass ratio was 1:120, so as to modify the surface of the multi-element low-melting-point alloy, form a Si monolayer on the alloy surface, and then take it out and dry it.
[0080] 7. The surface-modified low-melting-point alloy powder and high-density polyethylene powder were blended and ground in a mortar at a mass ratio of 1:5 to obtain a low-melting-point alloy / high-density polyethylene powder mixture, wherein the high-density polyethylene powder had a density of 1.95 g / cm 3 .
[0081] 8. A low melting point alloy / polyethylene mixture with a mass ratio of 20:80 was mixed with poplar fibers loaded with carbon nanotubes and nanosilver wires, and the mixture was fully mixed at a speed of 1500 rpm / min in a high-speed mixer, and then placed in a torque rheometer and mixed at a temperature of 160°C and a speed of 300 rpm / min for 40 minutes. After mixing, the mixture was taken out and crushed into a particle size of 100 mesh using a small pulverizer.
[0082] 9. Put the multi-component crushed mixed material into the mold, with a design format of 200×200mm, a paving thickness of 1.5mm, and a density of 2.0g / cm 3 It is formed by hot pressing on a flat vulcanizer at a temperature of 190°C, a pressure of 10 MPa, and a time of 12 minutes. During the hot pressing process, the low-melting-point alloy and high-density polyethylene melt, allowing the nano-conductive material and wood fiber to bond. The composite material is taken out after it is completely cooled and solidified.
[0083] 10. The prepared wood electrothermal composite material is applied with a low voltage of 8 to 24 V and a heating time of 10 to 12 minutes. The stable temperature can reach 54 to 141°C, the electrothermal radiation conversion efficiency is more than 97%, the temperature non-uniformity is less than 4°C, it has rapid heat transfer performance, a thermal conductivity of 0.84 to 1.0 W / (mK), and good flexural strength and water and weather resistance, with a flexural strength of 90 to 93 MPa and an internal bonding strength of 6.2 to 8.1 MPa. After accelerated aging with wet heat for 720 hours at a temperature of 65°C and a humidity of 85%, the electrothermal and mechanical properties are stable.
[0084] Comparative Example 1:
[0085] The delignified eucalyptus wood was not treated with (2), and the rest was the same as in Preparation Example 1, that is, the delignified wood whose wood fiber surface was not silanized participated in the subsequent treatment.
[0086] The prepared wood electrothermal composite material was subjected to a low voltage of 8 to 24 V, and the heating time was 10 to 12 minutes. The stable temperature could reach 37 to 92°C, the electrothermal radiation conversion efficiency was 86%, the temperature non-uniformity was less than 7°C, the thermal conductivity was 0.42 to 0.80 W / (mK), the bending strength was 61 to 73 MPa, and the internal bonding strength was 4.6 to 6.1 MPa. Since the wood fiber was not silanized, the interfacial bonding force between the wood fiber and the low melting point alloy and high-density polyethylene decreased. After accelerated aging for 720 hours at a temperature of 65°C and a humidity of 80%, the electrothermal stability and mechanical properties decreased.
[0087] Comparative Example 2:
[0088] The eucalyptus wood was not treated by (1), and the rest was the same as in Preparation Example 1, that is, the wood fiber was not delignified and directly participated in the subsequent treatment.
[0089] The prepared wood electrothermal composite material was subjected to a low voltage of 8 to 24 V, and the heating time was 10 to 12 minutes. The stable temperature could reach 33 to 86 ° C, the electrothermal radiation conversion efficiency was 85%, the temperature non-uniformity was less than 8 ° C, the thermal conductivity was 0.39 to 0.61 W / (mK), the bending strength was 59 to 7.0 MPa, and the internal bonding strength was 4.1 to 5.9 MPa. Since the poplar wood fiber was not delignified, the wood fiber was not easy to disperse and was easy to form agglomeration when mixed with multi-walled carbon nanotubes and nano-silver wires. In addition, the wood fiber had few hydrogen bonds on the surface without delignification, and the interface bonding force with low melting point alloy and high-density polyethylene was low. The temperature non-uniformity was poor. After 720 hours of wet heat accelerated aging at a temperature of 65 ° C and a humidity of 85%, the electrothermal stability and mechanical properties decreased significantly.
[0090] Comparative Example 3:
[0091] The high-density polyethylene was not mixed with the low-melting-point alloy, and the rest was the same as in Preparation Example 1.
[0092] The prepared wood electrothermal composite material is applied with a low voltage of 8 to 24 V and a heating time of 10 to 12 minutes. The stable temperature can reach 32 to 68°C, the electrothermal radiation conversion efficiency is 79%, the temperature non-uniformity is less than 12°C, the thermal conductivity is 0.89 to 1.2 W / (mK), the flexural strength is 46 to 72 MPa, and the internal bonding strength is 3.7 to 4.6 MPa. Since the high-density polyethylene is not mixed with the low-melting point alloy, the low-melting point alloy is an adhesive with poor bonding strength with the wood fiber and fails to form a tight bonding interface with the multi-walled carbon nanotubes and nano-silver wires, resulting in a lower resistive thermal effect, and the flexural strength and internal bonding strength are significantly reduced.
[0093] Comparative Example 4:
[0094] Sn 16 Bi 52 Pb 32 The alloy was not surface-modified with a silane coupling agent in step 6, and the rest was the same as in Preparation Example 1, that is, the wood fiber was not delignified and directly participated in the subsequent treatment.
[0095] The prepared wood electrothermal composite material is subjected to a low voltage of 8 to 24 V, and the heating time is 10 to 12 minutes. The stable temperature can reach 45 to 127°C, the electrothermal radiation conversion efficiency is 94%, the temperature non-uniformity is less than 5°C, and it has fast heat transfer performance, thermal conductivity of 0.82 to 0.98 W / (mK), bending strength of 75 to 83 MPa, and internal bonding strength of 4.7 to 6.5 MPa. Since the low-melting-point alloy is not silanized, a Si monolayer cannot be formed on the metal surface, and the low-melting-point alloy has a poor dispersion effect in the wood fiber matrix, and fails to cause the synergistic effect of conductive heating and enhanced mechanics.
[0096] It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. The present invention can be modified in various ways within the scope defined by the claims. New modifications obtained by combining different implementation methods or embodiments, as well as common technical means, etc., should also be considered to be included in the scope of the present invention.
Claims
1. A method for preparing a high-strength, aging-resistant wood-based electrothermal composite material. It is characterized in that include: (1) adjusting the pH value of a 2-5 wt% sodium chlorite aqueous solution to 4.6-5.0 by using 10-12 mol / L glacial acetic acid, immersing washed and dried wood fibers in the acid-adjusted sodium chlorite aqueous solution, wherein the material-liquid mass ratio is 1:(50-60), and then treating the fibers in a water bath at 40-45° C. for 2-3 h, taking the fibers out, washing, and drying the fibers to obtain delignified wood fibers; (2) Mixing delignified wood fiber and KH590 silane / acetone solution in a mass ratio of 1:(9-10) at 45-55°C for activation treatment for 4-6 hours, wherein the mass ratio of KH590 silane / acetone is (5-8):(25-40), so that the surface of the wood fiber is silanized, and then taking it out and leaving it for more than 1 hour to allow all the acetone to volatilize, and then drying it at 60-65°C for 6-8 hours; (3) slowly adding multi-walled carbon nanotubes and nanosilver wires in a mass ratio of 5:(2-5) into N,N-dimethylformamide, wherein the material-liquid mass ratio is (5-20):(80-95), magnetically stirring for 4-5 hours, and then performing water-soluble ultrasonic dispersion for 30-50 minutes, and then continuing magnetic stirring for 4-5 hours to obtain a multi-walled carbon nanotube / nanosilver wire mixed solution; (4) applying a multi-walled carbon nanotube / nanosilver wire mixed solution with a mass ratio of (10-30):(5-10) to the delignified wood fiber modified by silane by high-pressure atomization, mixing and dispersing for 30-50 minutes by a nano-disperser during the high-pressure atomization process to obtain a wood fiber loaded with multi-walled carbon nanotube / nanosilver wire, and drying the wood fiber at a temperature of 60-65° C. for 6-10 hours after taking it out; (5) The KH590 coupling agent and an ethanol aqueous solution with a concentration of 92-95 wt% are magnetically stirred at room temperature for 1-2 h to prepare a silane coupling agent / ethanol / water solution with a coupling agent mass fraction of 5-7%, and a powdered multi-component low melting point alloy Sn is added. 16 Bi 52 Pb 32 Add to silane coupling agent / ethanol / water solution and stir and blend for 15-40 minutes. The material-liquid mass ratio is 1:(100-120). The melting point of the alloy is 95-97°C and the density is 9.56-9.59 g / cm 3 , the mass ratio of Sn / Bi / Pb is (43-50):(6-9):(42-51), so as to modify the surface of the multi-element low melting point alloy, form a Si monolayer on the alloy surface, and then dry it after taking it out; (6) blending and grinding the surface-modified multi-element low-melting-point alloy and high-density polyethylene powder in a mass ratio of 1:(5-6) in a mortar to obtain a low-melting-point alloy / polyethylene mixture; (7) mixing a low melting point alloy / polyethylene mixture with a mass ratio of (5-20):(80-100) and wood fibers loaded with carbon nanotubes / nanosilver wires, and kneading the mixture at 150-160° C. for 30-40 min. After kneading, the mixture is taken out and crushed into a particle size of 100-300 meshes; (8) After the crushed mixture is paved, it is hot-pressed at a temperature of 180 to 190° C., a pressure of 5 to 10 MPa, and a time of 10 to 12 min, so that the low-melting-point alloy and the high-density polyethylene melt during the hot-pressing process, and the nano-conductive material and the wood fiber are bonded. After the mixture is completely cooled and solidified, the composite material is taken out to obtain the wood electrothermal composite material.
2. The preparation method according to claim 1, wherein In the method (1), the wood fiber is eucalyptus or poplar fiber, with a length distribution of 0.5-2.5 mm, a diameter distribution of 0.05-0.25 μm, an aspect ratio of 8-16, and is washed with deionized water and dried at 103-105° C. for 8-10 hours.
3. The preparation method according to claim 1, wherein In the method (3), the multi-walled carbon nanotubes have a length of 1 to 10 μm, a diameter of 8 to 50 nm, an inner diameter of 3 to 12 nm, the nanosilver wires have a length of 20 to 100 μm, a diameter of 20 to 90 nm, and a purity of 98%, and the multi-walled carbon nanotubes and nanosilver wires are added to N,N-dimethylformamide at a rate of 0.2 g / 10 s, and / or The magnetic stirring speed is 800-1500 rpm / min, and the ultrasonic frequency is 120-130 KHz.
4. The preparation method according to claim 1, wherein In the above (4), the high pressure atomization pressure is 0.2-0.7 MPa, The nano-disperser adopts ultrasonic high-frequency vibration mode, with a power of 600-800W, an ultrasonic frequency of 150-180KHz, a vibration frequency of 0.05-0.08Hz, and an amplitude of 100-150μm.
5. The preparation method according to claim 1, wherein In the above (5), the magnetic stirring speed is 800 to 1500 rpm / min, and the stirring and blending speed is 800 to 1500 rpm / min.
6. The preparation method according to claim 1, wherein In (5), the alloy has a melting point of 96°C and a density of 9.562 g / cm 3 , the Sn / Bi / Pb mass ratio is 48.6:6:45.
4.
7. The preparation method according to claim 1, wherein In the step (6), the powder is ground to a particle size of 100 to 300 meshes.
8. The preparation method according to claim 1, wherein In the above (7), kneading is performed in a torque rheometer at a rotation speed of 250 to 300 rpm / min.
9. The preparation method according to claim 1, wherein In the above (8), the paving density is 1.5 to 2.0 g / cm 3 .
10. A high-strength, ageing-resistant wood electrothermal composite material prepared by the preparation method according to any one of claims 1 to 9.